PEMBERDAYAAN MASYARAKAT EKONOMI KREATIF DALAM MENINGKATKAN SUMBER DAYA MANUSIA DI DESA MERBO - Pipit Afifah (EKSYDA: Jurnal Studi Ekonomi Syariah, 2020)
With the high growth expectations of the creative economy sector, we are faced with the challenge of being able to stimulate the creation of forms of creativity that have higher value. Various economic problems such as poverty and low quality of human resources and the level of competition in the labor market, education. This kind of condition indicates that the level of community education in Merbo Village is still low, which in the end also impacts on the low human resources in Merbo Village, causing the community in the village to be unable to live in prosperity and develop. As increasing natural resources is realizing the many potentials in Merbo Village to be developed into something more valuable and economically valuable, community groups who are members of the organization. The efforts of the Village government and Human Resources directly provide good conditions to improve the quality and capacity of the community in creating and assisting the development of Village development. This research is a qualitative descriptive which will describe the low human resources in Merbo Village, Mataram Baru.